A Integration of Holistic Care in Toddler Growth and Development - Asri Iman Sari; Ai Nur Zannah; Yuningsih (Jurnal Kesehatan dr. Soebandi, 2025)
Monitoring of children's growth and development is carried out periodically according to the child's age using the KIA and SDIDTK books to detect any problems or abnormalities that may occur in children. The objective of this study was to integrate holistic care, which was not yet included in the KIA and SDIDTK books, into the growth and development of toddlers in Jember Regency. The research method began with the creation of holistic instruments to monitor spiritual, cognitive, and artistic development appropriate to the age of the child, which were not yet available in the KIA book and SDIDTK guidelines. Those involved in the development of the instrument were lecturers specialising in child growth and development, professional midwife organisations, and practising midwives in the Jember Regency. The results obtained include holistic instruments for monitoring child growth and development as additional instruments in monitoring toddler growth and development, which have been implemented using the KIA and SDIDTK books. It was concluded that monitoring of children's growth and development should be carried out regularly using the KIA and/or SDIDTK books, with the addition of holistic SOPs on toddler growth and development.